Salivary Composition of Oral Squamous Cell Carcinoma Patients - Rehman, Arbab Zia Ur; amin, aleena; Irshad, Mohammad; Alam, Sheraz; Khan, Ismail Alam; Amin, Aleena (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: The purpose of the study was to determine the salivary composition of Oral squamous cell carcinoma patients. METHODOLOGY: A retrospective study was conducted over 6 months on data of 60 Oral squamous cell carcinoma patients obtained from the patient records of the Institute of Radiotherapy and Nuclear Medicine, Peshawar. Salivary pH, Sodium, Potassium, and total proteins of Oral squamous cell carcinoma patients were recorded. RESULTS: Sodium, Potassium, and total protein concentration in saliva of oral squamous cell carcinoma patients were 23.5 mM/L, 96.7mM/L, and 234.6 mM/L, respectively. These values were significantly higher than normal salivary concentration. CONCLUSION: It was concluded that the saliva of oral squamous cell carcinoma patients contains higher concentrations of Sodium, Potassium, and total proteins.